2016
DOI: 10.5966/sctm.2015-0238
|View full text |Cite
|
Sign up to set email alerts
|

Effective Hypothermic Storage of Human Pluripotent Stem Cell-Derived Cardiomyocytes Compatible With Global Distribution of Cells for Clinical Applications and Toxicology Testing

Abstract: To fully explore the potential of human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs), efficient methods for storage and shipment of these cells are required. Here, we evaluated the feasibility to cold store monolayers and aggregates of functional CMs obtained from different PSC lines using a fully defined clinical-compatible preservation formulation and investigated the time frame that hPSC-CMs could be subjected to hypothermic storage. We showed that two-dimensional (2D) monolayers of hPSC-CMs can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 64 publications
2
38
1
Order By: Relevance
“…These results suggest that thawed hPSC-CMs are especially vulnerable to single-cell culture, but may demonstrate improved long-term outcomes in host tissues or under tissue-like conditions. This inference is corroborated by a recent study that demonstrated hPSC-CMs cultured in 3D micro-tissue aggregates also are more resistant to prolonged hypothermic (4°C) storage-induced cell injury compared to their counterparts cultured in 2D monolayers [63]. However, differences in cryopreservation methodology may have also contributed to the observed differences, so these results must be interpreted with caution.…”
Section: Functional Recovery Of Stem Cell-derived Cardiomyocytes Asupporting
confidence: 55%
See 1 more Smart Citation
“…These results suggest that thawed hPSC-CMs are especially vulnerable to single-cell culture, but may demonstrate improved long-term outcomes in host tissues or under tissue-like conditions. This inference is corroborated by a recent study that demonstrated hPSC-CMs cultured in 3D micro-tissue aggregates also are more resistant to prolonged hypothermic (4°C) storage-induced cell injury compared to their counterparts cultured in 2D monolayers [63]. However, differences in cryopreservation methodology may have also contributed to the observed differences, so these results must be interpreted with caution.…”
Section: Functional Recovery Of Stem Cell-derived Cardiomyocytes Asupporting
confidence: 55%
“…Therefore, the long-term viability of hPSC-CMs at ultra-low storage temperatures should be evaluated, since this will be an important consideration in future biobanking initiatives. For very short-term storage, cryopreservation may not even be necessary, since recent evidence suggests that hPSC-CMs can be efficiently stored in hypothermic conditions (4°C) for up to 7 days without significantly compromising cell viability [63]. …”
Section: Considerations For the Cryopreservation Of Pluripotent Stmentioning
confidence: 99%
“…Monolayers of human hiPSC-CMs were fixed in 2% (v/v) glutaraldehyde in 0.1 M HEPES buffer (pH 7.4) for 20 min, washed in DPBS and stored in 1% (v/v) glutaraldehyde in DPBS until analyses. Samples were washed, contrasted, dehydrated, infiltrated, embedded, cured, dissected into small blocks and mounted on epon dummy blocks, as previously described 34 . Ultrathin sections of cell monolayers were cut on a Leica UC6 ultramicrotome using a diamond knife.…”
Section: Methodsmentioning
confidence: 99%
“…Human pluripotent stem cells have the potential to assist in the identification of genes associated with �a��alian develo�� genes associated with mammalian develop-s associated with mammalian develop-mammalian development (1,2), and the plasticity of stem cells suggests that they may have a wide range of clinical applications (3,4). Bone tissue engineering has also been explored for clinical purposes (5,6).…”
Section: Introductionmentioning
confidence: 99%